"If it helps someone, then I want to do it": Perspectives of persons living with dementia on research registry participation. (November 2020) - Lee, Jeanie YY; Crooks, Rachel E; Pham, Tram; Korngut, L; Patten, S; Jetté, N; Smith, EE; Roach, Pamela
Registries are an important platform to which persons with dementia and other cognitive impairments can contribute to research studies. Registries also provide an opportunity for patients to stay informed about current studies. Engaging patients in registry development can increase sustainability of a registry and patient retention in clinical registries. We sought the perspective of persons with dementia and their accompanying family members about their registry participation experiences, barriers and facilitators to participation, and potential avenues for improvement of registry processes such as recruitment, data collection, and knowledge translation. Two semi-structured focus groups with persons with dementia and their family members ( n = 18) were conducted and analyzed using thematic content analysis. Participants were recruited from an existing patient registry made up of patients currently being seen in a dementia assessment clinic. The main themes identified included altruistic motives with regards to registry participation; and access to and privacy of personal health information. As electronic health records are becoming more common, understanding barriers and facilitators from the perspectives of people with dementia is essential to inform the future development of cognitive condition-related registries. The results from our focus groups identified engagement strategies and solutions to overcome perceived barriers for individuals experiencing progressive cognitive decline to participate in longitudinal registry projects.